Effect of maternal weight gain according to the Institute of Medicine recommendations on pregnancy outcomes in a Chinese population. Issue 9 (September 2019) - Guan, Ping; Tang, Fei; Sun, Guoqiang; Ren, Wei
Objective: This study aimed to analyze the effects of maternal weight on adverse pregnancy outcomes. Methods: Data were retrospectively collected from a hospital in Wuhan, China. A total of 1593 pregnant women with singletons were included. Adverse outcomes during pregnancy, such as small for gestational age (SGA), large for gestational age (LGA), and hypertensive disorders in pregnancy (HDP) were analyzed. Results: The risks of low birth weight, SGA, and preterm birth were significantly higher in the inadequate gestational weight gain (GWG) group compared with the adequate GWG group. GWG over the guidelines was related to a higher risk of macrosomia, LGA, cesarean section, and HDP than GWG within the guidelines. The risks of low birth weight (OR = 5.082), SGA (OR = 3.959), preterm birth (OR = 3.422), and gestational diabetes mellitus (OR = 1.784) were significantly higher in women with a normal pre-pregnancy body mass index (BMI) and inadequate GWG compared with women with a normal pre-pregnancy BMI and adequate GWG. The risks of macrosomia (OR = 3.654) and HDP (OR = 1.992) were increased in women with normal pre-pregnancy BMI and excessive GWG. Conclusion: Women with an abnormal BMI and inappropriate GWG have an increased risk of adverse maternal and infant outcomes. Weight management during the perinatal period is required.